Unconventional Yeasts Are Tolerant to Common Antifungals, and Aureobasidium pullulans Has Low Baseline Sensitivity to Captan, Cyprodinil, and Difenoconazole - Electine Magoye; Maja Hilber-Bodmer; Melanie Pfister; Florian M. Freimoser (MDPI AG, 2020)
Many yeasts have demonstrated intrinsic insensitivity to certain antifungal agents. Unlike the fungicide resistance of medically relevant yeasts, which is highly undesirable, intrinsic insensitivity to fungicides in antagonistic yeasts intended for use as biocontrol agents may be of great value. Understanding how frequently tolerance exists in naturally occurring yeasts and their underlying molecular mechanisms is important for exploring the potential of biocontrol yeasts and fungicide combinations for plant protection. Here, yeasts were isolated from various environmental samples in the presence of different fungicides (or without fungicide as a control) and identified by sequencing the internal transcribed spacer (ITS) region or through matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry. Among 376 isolates, 47 taxa were identified, and Aureobasidium pullulans was the most frequently isolated yeast. The baseline sensitivity of this yeast was established for 30 isolates from different environmental samples in vitro to captan, cyprodinil, and difenoconazole. For these isolates, the baseline minimum inhibitory concentration (MIC50) values for all the fungicides were higher than the concentrations used for the control of plant pathogenic fungi. For some isolates, there was no growth inhibition at concentrations as high as 300 µg/mL for captan and 128 µg/mL for cyprodinil. This information provides insight into the presence of resistance among naturally occurring yeasts and allows the choice of strains for further mechanistic analyses and the assessment of A. pullulans for novel applications in combination with chemical agents and as part of integrated plant-protection strategies.